আওয়ামী লীগের শাসনকাল - নজরুল, আসিফ 1966- (Dhaka : Ananyā, 2014)
Articles on contemporary political issues of Bangladesh, chiefly during the government of Awami League.
In Bengali.
Keywords: Awami League; Bangladesh -- Politics and government -- 1971-